Is online shopping a trick or treat? understanding the perceptions of generation Z towards purchasing through tourism e-commerce platforms - Chin, Chee-Hua; Wong, Winnie Poh-Ming; Cham, Tat-Huei; Kumarusamy, Risidaxshinni (Asia Business Research Corporation, 2024)
The emergence and popularity of e-commerce have led to a significant shift in the way consumers purchase products and services, and Generation Z (Gen Z) are playing a key role in driving this trend. In Malaysia, the tourism industry has benefited from the growth of e-commerce platforms such as Agoda, Expedia, Klook, and Airbnb. This study examines the factors that influence zoomers' behavioural intention towards tourism e-commerce platforms in Malaysia, with a focus on trust as a moderating variable. Questionnaire data was collected from a sample of 162 university students in Sarawak, Malaysia and analysed using a partial least square structural equation modelling (PLS-SEM) approach. The estimation procedure was conducted using the WarpPLS 8.0. The findings revealed the significance of brand recognition and perceived quality in influencing zoomers’ trust, attitude, and intention to purchase through tourism e-commerce platforms. The positive moderating role of trust was also identified. These findings are essential for tourism practitioners to better understand the needs and wants of young e-customers. The study's insights are particularly aligned with and meaningful for Sarawak's digital economy initiatives. © 2024, Asia Business Research Corporation. All rights reserved.